MENERAPKAN METODE PEMBELAJARAN BEHAVIORISTIK DI ERA REVOLUSI PENDIDIKAN 4.0 - Faizin Faizin (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
The world of education in Indonesia is changing. This drastic change in the world of education was triggered, among other things, by the Covid-19 pandemic which first broke out in Wuhan, China, in 2019. Fundamental changes that have taken place in the world of education in Indonesia include changes in the teaching and learning process, namely from onsite learning to online learning. on line. The government calls these changes in terms of “Distance Learning”. This fundamental change immediately makes various aspects of the teaching and learning process required to adapt to the novelty of the situation, including in this case the behavioristic learning method which is also required to adapt to the conception of virtual learning. The behavioristic method is a classic method in the world of modern education. The main goal of today's behavioristic learning methods is to create changes in behavior so that they are able to fulfill 21st century skills. So how to apply behavioristic learning methods during a pandemic? That theme will be discussed in this research. In terms of objectives, this study intends to describe the application of behavioristic learning methods within an online education platform. This research uses a descriptive-qualitative method, using library research techniques to collect secondary data and interview techniques to collect primary data.